2023
DOI: 10.1007/s10914-022-09642-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphology of toothed whales (Cetacea, Odontoceti) as revealed by 3D skull geometry

Abstract: Extant odontocetes (toothed whales) exhibit differences in body size and brain mass, biosonar mode, feeding strategies, and diving and habitat adaptations. Strong selective pressures associated with these factors have likely contributed to the morphological diversification of their skull. Here, we used 3D landmark geometric morphometric data from the skulls of 60 out of ~ 72 extant odontocete species and a well-supported phylogenetic tree to test whether size and shape variation are associated with ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…A Procrustes fit was carried out to standardize the effects of size, orientation and positioning, with skulls aligned to their principal axis. Odontocete skulls are often asymmetric (Laeta et al., 2021), and previous studies have shown that the patterns of asymmetry can be complex (Galatius & Goodall, 2016) and show distinct variation patterns relative to symmetrical shape component (Vicari et al., 2023). Therefore, the asymmetrical component was separated from the symmetrical component for both dorsal and ventral analyses using the function ‘bilat.symmetry’ to average both sides of the skull across the midline.…”
Section: Methodsmentioning
confidence: 99%
“…A Procrustes fit was carried out to standardize the effects of size, orientation and positioning, with skulls aligned to their principal axis. Odontocete skulls are often asymmetric (Laeta et al., 2021), and previous studies have shown that the patterns of asymmetry can be complex (Galatius & Goodall, 2016) and show distinct variation patterns relative to symmetrical shape component (Vicari et al., 2023). Therefore, the asymmetrical component was separated from the symmetrical component for both dorsal and ventral analyses using the function ‘bilat.symmetry’ to average both sides of the skull across the midline.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous projects and applications have emerged, showcasing the effectiveness of photogrammetry and laser scanning in the realm of natural history digitization [11][12][13][14][15][16][17][18][19][20][21][22]. These initiatives have demonstrated the extensive array of possibilities and advancements within this field.…”
Section: Related Workmentioning
confidence: 99%
“…For example, an exemplary project [13] demonstrates the feasibility of using structured light scanners to capture field data and create high-resolution, interactive 3D models of at-risk natural history resources. Additionally, in a study involving toothed whales [21], 3D landmark geometric morphometric data were used from the skulls of 60 out of 72 extant odontocete species and a well-supported phylogenetic tree to test whether size and shape variation are associated with ecological adaptations at an interspecific scale.…”
Section: Related Workmentioning
confidence: 99%